Cholinergic actions of metrizamide. - Marder, E; O'Neil, M; Grossman, R I; Davis, K R; Taveras, J M (American Journal of Neuroradiology, 1983)
In a study of the possible mechanisms of the clinical side effects of metrizamide, it was applied to several in vitro model preparations. It was shown that, although high metrizamide concentrations are without noticeable effect on many basic neuronal functions, metrizamide does interfere with cholinergic mechanisms. At concentrations equivalent to, or significantly lower than, those probably achieved during clinical procedures, metrizamide is both an inhibitor of the enzyme acetylcholinesterase and an antagonist of cholinergic transmission. These data suggest the possibility that some of the side effects resulting from clinical procedures employing metrizamide may be explained by its actions on cholinergic synapses.